Corneal Abrasion Associated with Eyelash Extensions During General Anesthesia: A Case Report - Wang, Kuei-Fen; Wang, Li-Kai; Ho, Chun-Ning; Lan, Kuo-Mao; Chen, Jen-Yin (Archives of Clinical and Medical Case Reports, 2024)
Corneal abrasion is the most common ophthalmologic complication after general anesthesia. It is painful and might delay hospital discharge. Removal of eyelash extensions is not involved in the preoperative questionnaire currently. We report a young woman with eyelash extensions who underwent laparoscopic surgery under general anesthesia developed corneal abrasions perioperatively. In previous case reports, common adverse effects of eyelash extensions include keratoconjunctivitis, allergic blepharitis, and dry eyes. This is the first case report about corneal abrasion related to eyelash extensions. In the future, inclusion of eyelash extensions removal in peri-operative checklists must be considered.